„Pejzaże pamięci” jako dialog Agaty Tuszyńskiej i Isaaca Bashevisa Singera - Sobczak, Izabela (Przestrzenie Teorii, 2025)
The article analyzes Agata Tuszyńska’s Lost Landscapes: In Search of Isaac Bashevis Singer and the Jews of Poland (Singer. Pejzaże pamięci) and Familial History of Fear (Rodzinna historia lęku), in which landscape becomes a space of dialogue with the work of Isaac Bashevis Singer and a literary attempt to inscribe a private history. Intertextual references to Singer’s works serve not merely a stylistic function, but become a tool of affective participation in memory and shared Jewish identity. This dialogue takes on a spatial dimension in a dual sense: the landscape brings together a vision of pre-war, lost Poland with the real, post-war terrain marked by absence (R. Sendyka) and affect (H.U. Gumbrecht). In the spirit of Stanisław Balbus’s “reminiscence”, Tuszyńska does not compete with Singer but co-creates the narrative, complementing the modernist portrait. The landscape thus becomes not only an (auto)biographical gesture, but also a literary map of reclaiming voice and place within a community of memory.